Monkeypox: a public health emergency (Research, Society and Development, 2023)
Monkeypox (MPOX), is a viral zoonosis transmitted by contact with contaminated body material. The clinical Picture usually presents mild to moderate symptoms, such as fever, myalgia, fatigue, headache, asthenia, back pain and lymphadenopathy, with skin lesions being very characteristic signs of the disease and essential for identifying cases and excluding differential diagnoses. Suspected/probable/confirmed cases must be immediately notified, isolated and treated, and currently there is no specific treatment for the disease, being adopted the symptomatic conduct. Brazil registered 50,029 notifications, of which 10,247 were confirmed, 332 were probable, 3,548 were suspected and 35,902 were discarded, loss of follow-up and exclusions up to the 19th Epidemiological Bulletin. The present work sought to organize the main information on the disease, through an integrative review with the objective of elucidating in a clear and updated way the natural history of the disease and highlighting the epidemiological data in Brazil and in the city of São José dos Campos, São Paulo.